Representasi pustakawan dalam The Librarian Season 1 - Nadzir Cahyo Utomo; Christiani Lydia (Berkala Ilmu Perpustakaan dan Informasi, 2023)
Introduction. The success and acceptance of the community towards The Librarian Season 1, comic indirectly show an interest in the librarian profession. Although the library and librarian described in the Librarian Season 1 are fictional settings, the values in the world of librarianship cannot be ignored. This study aims to examine the representation of librarians in The Librarian Season 1 comic. Research Methods. The method used was qualitative. Collecting data was conducted by document study by exploring the website? Data Analysis. This paper used Roland Barthes' semiotic analysis focusing on the denotative, connotative, and myth levels. Results and Discussion. In the comic The Librarian Season 1, there are 13 episodes out of a total of 15 episodes that have librarian representation scenes based on ideal characters in the Basic Framework for Indonesian Librarianship (KDKI). Conclusion and Suggestions. Miche is a representation of the ideal character of a librarian based on KDKI. Therefore, the paper suggests that comic artists are considered to reproduce story ideas about librarians in comics, content, or other pop culture products. Librarian representation in the comic The Librarian Season 1 can be an alternative educational media for both prospective librarians and public.